Innovations to Make Glaucoma Surgery Safer - Kirti Singh (Delhi Journal of Ophthalmology)
The holy grail of a long surviving and safe trabeculectomy is still awaited. Modifications in the conventional trabeculectomy are required to increase the efficacy of the procedure, reduce the complications and minimize the bleb induced discomfort. Three of the innovations successfully used for over a decade are described in this paper, namely modified conjunctival incision, novel manual SICS trabeculectomy scleral incision and use of amniotic membrane as an anti-fibrotic adjunct in trabeculectomy.